Tensor Algebras of Bimodules and Their Representations - Gubareni, Nadiya (Sarajevo Journal of Mathematics, 2024)
We study (D,O)-species, which are a special case of species introduced by Yu. A. Drozd (1980). The representations of (D,O)-species and modules over the corresponding tensor algebras of bimodules are considered. We find necessary and sufficient conditions on a special kind of (D,O)-species under which they are of bounded representation type. The conditions are given in terms of Dynkin diagrams and diagrams with weights. The connection of these (D,O)-species and corresponding tensor algebras with right hereditary semiperfect and semidistributive rings are studied. * This paper was presented at the International Scientific Conference Graded structures in algebra and their applications, dedicated to the memory of Prof. Marc Krasner, IUCDubrovnik, Croatia, September, 22-24, 2016.